Tissue loss disease outbreak significantly alters the Southeast Florida stony coral assemblage - Hayes, Nicole K.; Walton, Charles J.; Gilliam, David S. (Frontiers in Marine Science, 2022)
A stony coral tissue loss disease (SCTLD) outbreak, first widely reported in 2014 in the Southeast Florida Ecosystem Conservation Area (Coral ECA), has continued to impact stony coral communities for more than seven years. Here, we utilize long-term (2012-2020) annual monitoring data from the Southeast Florida Reef Evaluation and Monitoring Project (SECREMP) to assess the impact of the SCTLD outbreak on the stony coral assemblage as well as spatiotemporal and ecological associated variation. Furthermore, we expand upon previously documented disease event-related regional impacts. Coral ECA SCTLD prevalence was greatest in 2016 coinciding with significant declines in coral live tissue area (LTA). Even though by 2018 SCTLD prevalence had dropped to < 1% and significant annual LTA declines were no longer recorded, upwards of 59% of stony coral total LTA in the Coral ECA was lost between 2015-2018. SCTLD was observed across all habitats and affected 11 stony coral species. Colony size did not preclude infection or mortality, with 25% of all infections occurring on colonies 5-14 cm in diameter. The indiscriminate nature of the disease and lack of size refugia has altered the stony coral population structure and assemblage composition. Since 2016, the coral assemblage has shifted towards smaller colonies, with a significant decrease in mean colony size. Juvenile corals, < 4 cm diameter, of many reef building, structurally-complex species were rarely documented, while eurytopic, generalist species dominated juvenile abundance. Although significant losses, altering ecosystem function, were documented, all species recorded prior to the disease event were present, albeit some only as juveniles. Our study adds to the growing body of evidence of the severity of the disease outbreak and precarious state of the stony coral assemblage in the Coral ECA. We show long-term monitoring projects provide invaluable opportunities to capture such spatiotemporal changes in coral assemblages and may identify potential indicators of recovery. While no stony coral species were completely lost from the monitored assemblage, the likelihood of recovery, to even a pre-outbreak state, is limited without immediate action addressing development related local stressors and climate change related global stressors.